Patterns of intracolumnar size variation inform the heterochronic mechanisms underlying extreme body shape divergence in microcephalic sea snakes. Issue 3 (15th November 2019) - Sherratt, Emma; Sanders, Kate L.
Abstract: Sea snakes (Hydrophiinae) that specialize on burrowing eel prey have repeatedly evolved tiny heads and reduced forebody relative to hindbody girths. Previous research has found that these "microcephalic" forms have higher counts of precaudal vertebrae, and postnatal ontogenetic changes cause their hindbodies to reach greater girths relative to their forebodies. We examine variation in vertebral size along the precaudal axis of neonates and adults of three species. In the nonmicrocephalic Hydrophis curtus, these intracolumnar patterns take the form of symmetrical curved profiles, with longer vertebrae in the midbody (50% of body length) relative to distal regions. In contrast, intracolumnar profiles in the microcephalic H. macdowelli and H. obscurus are strongly asymmetrical curves (negative skewness) due to the presence of numerous, smaller‐sized vertebrate in the forebody (anterior to the heart). Neonate and adult H. macdowelli and H. obscurus specimens all exhibit this pattern, implying an onset of fore‐ versus hindbody decoupling in the embryo stage. Based on this, we suggest plausible developmental mechanisms involving the presence and positioning of Hox boundaries and heterochronic changes in segmentation. Tests of our hypotheses would give new insights into the drivers of rapid convergent shifts in evolution, but will ultimately require studies of gene expression in the embryos of relevant taxa. Abstract : The pattern of intracolumnar vertebral size differs markedly between microcephalic sea snake species Hydrophis macdowelli and H. obscurus, and non‐microcephalic species H. curtus. Plotting relative length of each pre‐cloacal vertebra along the column reveals an asymmetrical profile that is unique to microcephalic species, where the vertebrae anterior to the heart (marked by arrow) are more numerous than in H. curtus and increase in size more gradually toward the middle of the body. A simplified schematic (below) illustrates the different intracolumnar profiles, highlighting the number of smaller‐sized vertebrae anterior to the heart characteristic of microcephalic species. Research Highlights: Dramatic body shape shifts in response to dietary specializations in sea snakes are accompanied by asymmetrical, left‐skewed profiles of intracolumnar vertebral size that have not been reported in any other studied snake. Neonate and adult specimens both exhibit skewed intracolumnar profiles, implying heterochronic changes that have not been previously been described in snake embryos. Testable hypotheses involving homeotic and somitogenetic effects are provided for the evolutionary development of extreme body shapes in sea snakes.